Toxicological effects of acute prothioconazole and prothioconazole-desthio administration on liver in male Chinese lizards (Eremias argus). (March 2022) - Xie, Yun; Chang, Jing; Pan, Yifan; Hao, Weiyu; Li, Jianzhong
Abstract: Prothioconazole (PTC) is a high effective systemic fungicide, and one of its major metabolites is prothioconazole-desthio (PTC-d). Because of its wildly use in the farmland of China, the local eco-toxicological effects of PTC as well as PTC-d are needed to be concerned. This study investigated hepatoxicity of Chinese lizards ( Eremias argus ), a local non-target organism, after single dose oral treated (100 mg kg −1 BW) through pathological, enzyme activity and gene expression analysis. PTC treatment caused ballooning and PTC-d treatment led to macrovesicular steatosis of hepatocyte. The elevation of serum indexes, including the activities of aspartate aminotransferase (AST), alkaline phosphatase (ALP) and alanine aminotransferase (ALT), further confirmed the hepatic injury. PTC and PTC-d treatments altered oxidative status reflected by the inhibition of superoxide dismutase (SOD) activity, meanwhile, the stimulation of catalase (CAT) activity, glutathione peroxidase (GPx) activity and malondialdehyde (MDA) content. The mRNA expression changes of apoptosis-related factors and cytokines genes, including Bax, Bcl-2, TNF-α, NF-κB, Caspase-3 and Nrf2, deeply uncovered the potential mechanism of hepatotoxicity caused by PTC and PTC-d. In brief, the results indicated that both of these two compounds altered oxidative status, then were likely to trigger caspase-3 by affecting the ratio of pro- and anti-apoptotic factors which belong to intrinsic apoptosis pathway. Specifically, more serious impacts were induced by PTC-d than its parent compound. This study is the first to provide specific insight into potential hepatotoxicity resulted from PTC and PTC-d in male Chinese lizards. Graphical abstract: Image 1 Highlights: PTC led to ballooning while PTC-d led to macrovesicular steatosis of hepatocyte in male lizards. PTC and PTC-d elevated serum aminotransferase activities and altered hepatic oxidative status. The RNA expression changes of Bax/Bcl-2 ratio and Caspase-3 indicated intrinsic apoptosis. More serious impacts were induced by PTC-d than its parent compound PTC.